2003
DOI: 10.1128/aem.69.10.6201-6207.2003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Holding Time and Temperature on Escherichia coli Densities in Surface Water Samples

Abstract: Escherichia coli is a routinely used microbiological indicator of water quality. To determine whether holding time and storage conditions had an effect on E. coli densities in surface water, studies were conducted in three phases, encompassing 24 sites across the United States and four commonly used monitoring methods. During all three phases of the study, E. coli samples were analyzed at time 0 and at 8, 24, 30, and 48 h after sample collection. During phase 1, when 4°C samples were evaluated by Colilert or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 4 publications
2
40
1
7
Order By: Relevance
“…Equipment was maintained in sterile condition by flame sterilization (Myers et al 2007). Holding time tests confirmed previous studies that indicated minimal changes in E. coli and total coliform concentrations within 24 h of collection if samples are held unfrozen below 10°C (Myers et al 2007;Bordner and Winter 1978;Pope et al 2003).…”
Section: Sample Collection and Analysessupporting
confidence: 67%
“…Equipment was maintained in sterile condition by flame sterilization (Myers et al 2007). Holding time tests confirmed previous studies that indicated minimal changes in E. coli and total coliform concentrations within 24 h of collection if samples are held unfrozen below 10°C (Myers et al 2007;Bordner and Winter 1978;Pope et al 2003).…”
Section: Sample Collection and Analysessupporting
confidence: 67%
“…For the current study, we had to relax these requirements to permit use of auto-samplers (without carousel chilling), which were triggered automatically by events. Pope et al (2003) found that E. coli concentrations in samples held at less than 108C were generally consistent with those measured within 8 h. Similarly, Stadler et al (2008) reported only minor sample deterioration for holding temperatures of around 58C. So the main issue is the holding time within the instrument shack, after collection, but before auto-samples were retrieved and stored on ice.…”
Section: Autosampler Quality Assurancementioning
confidence: 82%
“…Pope et al 2003;Stadler et al 2008) and cross-contamination through carry-over from residues in the sampler pipework and mechanisms (e.g. Anderson & Rounds 2010;Solo-Gabriele et al 2000).…”
Section: Autosampler Quality Assurancementioning
confidence: 99%
“…Furthermore, there is limited and inconsistent scientific evidence supporting these policies, none of which is specific to groundwater samples. Previous studies have investigated surface water (lakes and rivers, often those receiving municipal or agricultural waste) (Standridge and Lesar 1977;Dutka and El-Shaarawi 1980;Pope et al 2003;Aulenbach 2010), municipal and industrial effluent (Standridge and Lesar 1977;Dutka and El-Shaarawi 1980;Selvakumar et al 2004), stormwater (Selvakumar et al 2004), and water from within municipal distribution systems (McDaniels et al 1985). Survival rates were variable for different fecal indicator bacteria (FIB), with total coliforms often decreasing shortly after collection (Mendez Novelo et al 2010), whereas fecal coliforms generally survived longer, possibly up to 62 h (Aulenbach 2010).…”
mentioning
confidence: 99%
“…Survival rates were variable for different fecal indicator bacteria (FIB), with total coliforms often decreasing shortly after collection (Mendez Novelo et al 2010), whereas fecal coliforms generally survived longer, possibly up to 62 h (Aulenbach 2010). Some studies observed significant decreases in Escherichia coli (E. coli) density by 18Á24 h (Selvakumar et al 2004, Aulenbach 2010, while other studies suggested that up to 48 h was acceptable (Pope et al 2003). Notably, across all of these studies, there was very little power to analyze holding times greater than 48 h.…”
mentioning
confidence: 99%